Contact manufacturing method, contact and interrupter

By forming grooves with a longer depth than width on the contact surface, the problem of lowering bond strength in ultrasonic bonding is solved, and more efficient bonding and more stable bonding surfaces are achieved.

CN113874974BActive Publication Date: 2025-02-25MITSUBISHI ELECTRIC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN201980096749.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-06-04
Publication Date
2025-02-25
Estimated Expiration
2039-06-04

AI Technical Summary

Technical Problem

When using ultrasonic bonding method, the bottom surface of the concave contacts oxidize to form an oxide film, resulting in a decrease in bonding strength or a non-bonding state.

Method used

The grooves formed on the surface of the contact having a depth longer than the width from the surface of the contact, the grooves include portions buried with the material of the contact and the base on the surface side, and make the material and oxide more internal than the surface side Mixed section.

Benefits of technology

Through the groove structure, bonding strength is improved, the formation of an oxide film is suppressed, and the stability of bonding is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113874974B_ABST
    Figure CN113874974B_ABST
Patent Text Reader

Abstract

The purpose of the present disclosure is to provide a contact piece in which there is no oxide film between the bonding surfaces of the base and the contact and the bonding property between the contact and the base is improved. The manufacturing method of the contact piece disclosed in the present disclosure is characterized by comprising: a step of forming a groove portion whose depth is longer than the width from the surface of the contact; a step of placing the base on a mounting table of an ultrasonic bonder; a step of placing the contact on the base on the mounting table in a manner that the base and the surface forming the groove portion are in contact; a step of bringing an ultrasonic horn of the ultrasonic bonder into contact with the contact; and a step of applying ultrasonic energy from the ultrasonic horn to bond the contact and the base.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for manufacturing a contact having a base and a contact point, and the contact. Background Art

[0002] A contactor including a breaker and an interrupter includes contact pieces as movable contacts and fixed contacts, and the contact pieces include contact points and a base to which the contact points are engaged.

[0003] In the past, as a method for joining a base and a contact, a brazing method using a solder was used. In recent years, an ultrasonic bonding method has been used. The ultrasonic bonding method is a method in which a contact is overlapped to a predetermined position on the upper surface of a base including a metal plate and abutted against an ultrasonic horn, thereby removing an oxide film covering the joining surface of the contact and the base by ultrasonic vibration, and temporarily fixing the contact and the base. For example, if the ultrasonic bonding method is used in joining a contact mainly composed of Ag and a base mainly composed of Cu, the oxide film covering the joining surface of the contact and the base is removed by ultrasonic vibration, and an alloy of Ag and Cu is formed by metal diffusion reaction to perform the joining. In addition, a contact in which a recess is formed on the joining surface side with the base in an ultrasonically joined base and contact is disclosed (for example, refer to patent document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 3-156815 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, if a recess is formed in the contact in this way, the timing of contacting the base is different between the bottom surface of the recess and the upper surface of the recess. The upper surface of the recess contacts the base earlier than the bottom surface of the recess, so the ultrasonic energy based on the ultrasonic vibration is concentrated, making it easy to remove the oxide film. On the other hand, with respect to the bottom surface of the recess, the ultrasonic energy is not sufficiently transmitted, so it is necessary to abut the ultrasonic horn until the upper surface of the recess softens and the bottom surface of the recess contacts the base. During the period of abutting the ultrasonic horn until the bottom surface of the recess contacts the base, the friction heat of the upper surface of the recess is transferred to the bottom surface of the recess, thereby oxidizing the bottom surface of the recess to form an oxide film. The oxide film is between the joint surface of the contact and the base, resulting in a reduction in the joint strength or a non-joining state.

[0009] The present disclosure has been made to solve the above-mentioned problems, and an object of the present disclosure is to provide a contact that suppresses the presence of an oxide film between the bonding surfaces of a contact and a base and improves the bonding properties between the contact and the base.

[0010] Means for solving problems

[0011] The manufacturing method of the contact piece disclosed in the present invention is characterized by comprising: a step of forming a groove portion on the surface of the contact point, the depth of which is longer than the width from the surface of the contact point; a step of placing a base on a mounting table of an ultrasonic joiner; a step of placing the contact point on the base on the mounting table in a manner such that the base and the surface formed with the groove portion are in contact; a step of making an ultrasonic horn of the ultrasonic joiner contact the contact point; and a step of applying ultrasonic energy from the ultrasonic horn to join the contact point and the base.

[0012] The contact disclosed in the present invention is characterized in that, in a contact having a base and a contact ultrasonically bonded to the base, a groove is formed on the surface of the contact, and the groove includes: a portion buried with a material of at least one of the contact and the base on the surface side; and a portion in which the material and the oxide are mixed more internally than the surface side.

[0013] The interrupter disclosed in the present invention is characterized in that it comprises: a contact piece, in which a groove is formed on the surface of the contact piece having a base and a contact ultrasonically bonded to the base, and the groove includes a portion buried with a material of at least one of the contact and the base on the surface side and a portion in which the material and the oxide are mixed more internally than the surface side; a contact table that contacts the contact in a closed state; and a drive control device that drives the base to open and close the contact piece.

[0014] Effects of the Invention

[0015] According to the method for manufacturing a contact disclosed in the present invention, a groove whose depth is greater than its width is formed on the surface of the contact, thereby improving the bonding strength between the base and the contact and efficiently manufacturing the contact.

[0016] According to the contact piece disclosed in the present invention, a groove is formed on the surface of the contact, and includes a portion on the surface side of the contact partially buried with the material of the contact and a portion in which the materials of the contact and the base are mixed with oxides more internally than the surface side, thereby being able to improve the bonding strength between the base and the contact.

[0017] According to the interrupter disclosed in the present invention, a groove is formed on the surface of the contact, and includes a portion on the surface side of the contact partially buried with the material of the contact and a portion in which the materials of the contact and the base are mixed with oxides more internally than the surface side, thereby improving the bonding strength between the base and the contact and making it more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is an example of a schematic diagram showing a contact including a contact point and a base before ultrasonic bonding according to the first embodiment.

[0019] Figure 2This is an example of a flowchart showing a manufacturing process of a contact including a contact point and a base according to the first embodiment.

[0020] Figure 3 Yes and through Figure 2 An example of a schematic diagram corresponding to the manufacturing process of a contact is shown.

[0021] Figure 4 is from Figure 1 The TT cross-sectional view after ultrasonic bonding as viewed in the z direction shows only one groove portion.

[0022] Figure 5 is from Figure 1 Cross-sectional view of SS after ultrasonic bonding, viewed in the x-direction.

[0023] Figure 6 The table shows the measurement results of the bonding strength between the contact point and the base after ultrasonic bonding in each pattern in which the length of the groove portion and the distance between the groove portions were changed.

[0024] Figure 7 is based on Figure 6 The table shown in FIG. 1 is a graph in which the vertical axis represents the bonding strength (MPa) and the horizontal axis represents ta / t.

[0025] Figure 8 In the case of modes 1 to 5, Figure 1 TT cross-sectional view after ultrasonic bonding as viewed in the z direction.

[0026] Fig. 9 In the case of modes 1 to 5, Figure 1 This is a cross-sectional view of the SS after ultrasonic bonding, viewed in the direction of the arrow x.

[0027] Fig.10 In the case of modes 6 to 10, Figure 1 TT cross-sectional view after ultrasonic bonding as viewed in the z direction.

[0028] Fig.11 In the case of mode 6, Figure 1 This is a cross-sectional view of the SS after ultrasonic bonding, viewed in the direction of the arrow x.

[0029] Fig.12 In the case of mode 10, Figure 1 This is a cross-sectional view of the SS after ultrasonic bonding, viewed in the direction of the arrow x.

[0030] Fig.13 In the case of modes 11 to 15, Figure 1 TT cross-sectional view after ultrasonic bonding as viewed in the z direction.

[0031] Fig.14 In the case of mode 15, Figure 1 This is a cross-sectional view of the SS after ultrasonic bonding, viewed in the direction of the arrow x.

[0032] Fig.15 In the case of modes 16 to 20, Figure 1 TT cross-sectional view after ultrasonic bonding as viewed in the direction of the arrow x.

[0033] Fig.16 In the case of modes 16 to 20, Figure 1 This is a cross-sectional view of the SS after ultrasonic bonding, viewed in the direction of the arrow z.

[0034] Fig.17 This is an example of a groove portion having a different shape from that of patterns 1 to 20. Figure 1 TT cross-section viewed in the direction of the z arrow.

[0035] Fig.18 This is another example of a groove shape different from that of the patterns 1 to 20. Figure 1 This is a cross-sectional view of the SS after ultrasonic bonding, viewed in the direction of the arrow x.

[0036] Fig.19 It is a schematic diagram of an example of a switch equipped with the contactor of this embodiment.

[0037] (Explanation of Reference Numerals)

[0038] 1: contact point; 1a: groove; 2: base; 5: joint surface; 6: contact piece; 8: contact platform; 9: drive control device. DETAILED DESCRIPTION

[0039] Implementation method 1.

[0040] The contact according to this embodiment will be described. Figure 1 An example of a schematic diagram of the contact 6 before ultrasonic bonding according to the present embodiment is shown.

[0041] like Figure 1 As shown, the contact element 6 includes a contact point 1 and a base 2 .

[0042] The material of the contact 1 is, for example, mainly composed of Ag and containing W and C. The material of the base 2 is, for example, mainly composed of Cu and containing Sn, Zn, Cr, Fe, W, and C.

[0043] A groove 1a is formed on the surface of the contact 1, the depth of which is greater than the width of the contact 1. Figure 1, a case where a plurality of grooves 1a are formed at intervals in the width direction of the grooves 1a is shown. The surface of the contact 1 having the grooves 1a formed thereon is a joining surface 5 as a surface where the contact 1 and the base 2 are joined.

[0044] In this embodiment, the length of the contact 1 in the x direction, which is the width direction of the groove 1a, is represented by wa, the length of the contact 1 in the y direction, which is the depth direction of the groove 1a, is represented by ta, and the length of the contact 1 in the z direction, which is the depth direction of the groove 1a and the direction perpendicular to the width direction of the groove 1a, is represented by ha. In addition, the depth of the groove 1a is represented by t. The interval between the grooves 1a in the width direction of the groove 1a is represented by w. The length of the base 2 in the x direction is represented by wb, the length of the base 2 in the y direction is represented by tb, and the length of the base 2 in the z direction is represented by hb.

[0045] use Figure 2 and Figure 3 A description will be given of a process for manufacturing the contact 6 according to the present embodiment using an ultrasonic bonder.

[0046] Figure 2 This is an example of a flowchart showing a manufacturing process of the contact 6 according to the present embodiment using an ultrasonic bonder. Figure 3 is and in Figure 2 The example of the schematic diagram corresponding to the manufacturing process of the contact 6 is shown in FIG. Figure 2 During the manufacturing process, the Figure 1 The contact element 6 is shown in FIG.

[0047] The ultrasonic bonder used in the manufacturing process includes a mounting table 3 and an ultrasonic horn 4. The mounting table 3 and the ultrasonic horn 4 are made of, for example, SUS material. In addition, the mounting table 3 and the ultrasonic horn 4 may also be coated with a high melting point material including carbon, DLC (Diamond Like Coating), Ti, W, and Mo so as not to adhere to the contact member 6 due to metal diffusion reaction during ultrasonic bonding.

[0048] exist Figure 2 In step S101, Figure 3 As shown in a, a groove portion 1a is formed on the surface of the contact 1, wherein the depth from the surface of the contact 1 is longer than the width.

[0049] exist Figure 2 In step S102, as Figure 3 As shown in b, the base 2 is placed and fixed on the mounting table 3 of the ultrasonic bonder.

[0050] exist Figure 2 In step S103, Figure 3As shown in c, the contact 1 is placed on the base 2 on the mounting table 3 of the ultrasonic bonder so that the base 2 and the surface of the contact 1 formed with the groove 1a are in contact with each other.

[0051] exist Figure 2 In step S104, Figure 3 As shown in d, the ultrasonic horn 4 of the ultrasonic bonder is brought into contact with the contact point 1.

[0052] exist Figure 2 In step S105, Figure 3 As shown in FIG. 8 , ultrasonic energy is applied from the ultrasonic horn 4 at an arbitrary load and for an arbitrary time to join the contact point 1 and the base 2 . Figure 3 The arrow Y in FIG. 5 shows the state of operating the ultrasonic horn 4. When the ultrasonic horn 4 is in contact and operated, a joint surface 5 is formed between the contact point 1 and the base 2.

[0053] exist Figure 2 In step S106, Figure 3 As shown in FIG. 5 , the ultrasonic horn 4 is lifted up, and the contact 6 on which the contact point 1 and the base 2 are bonded via the bonding surface 5 is taken out from the mounting table 3 of the ultrasonic bonder to complete the process.

[0054] Next, the groove portion 1 a after ultrasonic bonding will be described.

[0055] Figure 4 Only shows Figure 1 A groove portion 1a in the TT cross-sectional view after ultrasonic bonding as viewed in the z direction. Figure 5 is from Figure 1 Cross-sectional view of SS after ultrasonic bonding, viewed in the x-direction.

[0056] exist Figure 4 and Figure 5 The t1 portion as the surface side of the contact 1 shown in FIG. 1 is seamlessly filled with the material of the metal component contained in the material of the contact 1 due to the plastic flow of the contact 1. On the other hand, the t2 portion further inside than the surface side is mixed with the material of the metal component contained in the materials of the contact 1 and the base 2 and the oxide 7.

[0057] That is, the groove 1a after ultrasonic bonding includes: a t1 portion filled with the metal component material included in the material of the contact 1; and a t2 portion where the metal component material included in the materials of the contact 1 and the base 2 and the oxide 7 are mixed.

[0058] The oxide 7 present in the t2 portion is generated by: a natural oxide film of the joint 1 and the base 2 before ultrasonic joining; and an oxide film formed on the joining surface 5 due to frictional heat during ultrasonic joining and repelled by plastic flow of the joining surface 5 due to minute sliding caused by ultrasonic energy.

[0059] In order to measure the bonding strength corresponding to the grooves 1 a formed before ultrasonic bonding, experiments of patterns 1 to 20 were conducted by changing the number of grooves 1 a , the depth t, and the interval w between the grooves 1 a .

[0060] In the experiments with modes 1 to 20, the shape of the groove 1a formed in the joint 1 before ultrasonic bonding is a straight slit shape in the depth direction of the groove 1a. In addition, the length of the groove 1a in the depth direction is equal to the length ha of the joint 1 in the z direction which is the depth direction of the groove 1a.

[0061] In the experiments of modes 1 to 20, the length wa of the contact 1 in the x direction is 10 mm, the length ta in the y direction is 1 mm, and the length ha in the z direction is 5 mm. The length wb of the base 2 in the x direction is 15 mm, the length tb in the y direction is 5 mm, and the length hb in the z direction is 10 mm.

[0062] In addition, the width of the groove portion 1 a is, for example, approximately 10 μm.

[0063] The bonding strength is measured by ultrasonically bonding the contact 1 and the base 2, and then pressing a load detector tool with a force sensor on the side of the contact 1. After breaking, the bonding strength (N) is divided by the area of ​​the bonding surface 5 to calculate the bonding strength per unit area (MPa).

[0064] In the experiments with modes 1 to 20, the area of ​​the joint surface 5 is wa×ha=5mm×10mm=50mm 2 .

[0065] The connection between the contact 1 and the base 2 was performed in the atmosphere. The ultrasonic bonder used had a frequency of, for example, 50 kHz or more and 200 kHz or less in the experiments with modes 1 to 20. The bonding time can be arbitrarily changed according to the frequency and output.

[0066] In the present embodiment, the surface roughness Ra of the bonding surface 5 is 5 μm ≤ Ra < 20 μm. The surface roughness Ra is an index of surface roughness standardized in JIS B 0601-2001 (ISO 4287-1997), and means arithmetic mean roughness.

[0067] The criterion for judging the quality of the joint strength is 50 MPa. If the measured joint strength is less than 50 MPa, it is judged as insufficient strength, and if it is 50 MPa or more, it is judged as having sufficient strength. The judgment criterion 50 MPa is the average joint strength in the case of solder jointing performed in the past.

[0068] Furthermore, if the bonding strength is 70 MPa or more, it is judged that the bonding strength is excellent. 70 MPa, which is a criterion for judging excellent bonding strength, is a value obtained by performing experiments of Patterns 1 to 20.

[0069] Figure 6 This is a table showing the measurement results of the bonding strength between the contact 1 and the base 2 after ultrasonic bonding in each mode in which the depth t of the groove 1a before ultrasonic bonding and the interval w between the grooves 1a were changed. Figure 6 In the table, a case where the bonding strength is less than 50 MPa, which is a criterion for judging whether the bonding strength is good or bad, is indicated as ×; a case where the bonding strength is greater than 50 MPa and less than 70 MPa is indicated as 0; and a case where the bonding strength is greater than 70 MPa, which is a criterion for judging whether the bonding strength is excellent, is indicated as ◎.

[0070] Figure 7 Shown based on Figure 6 The table shown is a graph in which the vertical axis represents the bonding strength (MPa) and the horizontal axis represents ta / t. Figure 7 The range A shows a range of ta / t of 70 MPa or more, which indicates excellent bonding strength. Figure 7 The boundary B shows a criterion for determining excellent bonding strength.

[0071] In addition, for comparison, the result of the case where the number of grooves 1a is 0, that is, there is no groove 1a, is taken as Comparative Example 1. Figure 6 The bonding strength without the groove 1a was 31 MPa, which was lower than the quality judgment standard of 50 MPa.

[0072] For each mode, in order to facilitate understanding, refer to Figure 6 The table, while using Figure 8 to Figure 14 Provide explanation.

[0073] First, use Figure 8 and Fig. 9 Modes 1 to 5 are described below.

[0074] Figure 8 Is set as in Figure 1 As shown in the schematic diagram of the contact piece, the grooves 1a of the patterns 1 to 5 are formed before ultrasonic bonding. Figure 1 TT cross-sectional view after ultrasonic bonding as viewed in the z direction. Fig. 9Is set as in Figure 1 As shown in the schematic diagram of the contact piece, the grooves 1a of the patterns 1 to 5 are formed before ultrasonic bonding. Figure 1 The SS cross-sectional view after ultrasonic bonding as viewed in the direction of the arrow x in FIG. The cross-sectional view is also used in the description of the experimental results of the model described later.

[0075] In Modes 1 to 5, before ultrasonic bonding, w = 1.7 mm, wa / w = 5.9. ta / t is 21.3 in Mode 1, 20.0 in Mode 2, 12.5 in Mode 3, 8.5 in Mode 4, and 8.0 in Mode 5.

[0076] The measurement results of the bonding strengths of Patterns 1 to 5 are described in order.

[0077] All of Modes 1 to 5 are 50 MPa or more and less than 70 MPa, and have sufficient strength.

[0078] It is considered that the reason why it is not 70 MPa or more although it is 50 MPa or more and less than 70 MPa is that the number of grooves 1a is greater than that of other modes, and the grooves 1a are not filled with oxide 7 to form a partial space, so the non-bonded portion P with the base 2 increases.

[0079] use Figure 10 to Figure 12 Explain modes 6 to 10.

[0080] Fig.10 is from Figure 1 TT cross-sectional view after ultrasonic bonding as viewed in the z direction.

[0081] For modes 6 to 10, before ultrasonic bonding, w = 2.0 mm, wa / w = 5.0. ta / t was set to 21.3 in mode 6, 20.0 in mode 7, 12.5 in mode 8, 8.5 in mode 9, and 8.0 in mode 10.

[0082] The measurement results of the bonding strengths of Patterns 6 to 10 are described in sequence.

[0083] In modes 7 to 9, the bonding strength is 70 MPa or more, which is high strength. This is considered to be because the inside of the groove 1 a is filled with the oxide 7 , so that no oxide 7 remains on the bonding surface 5 .

[0084] In mode 6, the bonding strength is 50 MPa or more and less than 70 MPa, which is sufficient strength but not 70 MPa or more. Fig.11 In case of mode 6, Figure 1 This is a cross-sectional view of the SS after ultrasonic bonding, viewed in the direction of the arrow x.

[0085] It is believed that if the depth t of the groove 1a formed before ultrasonic bonding is too small, the oxide 7 will be filled in the groove 1a after ultrasonic bonding, and further, the oxide 7 above it will remain on the bonding surface 5, so the bonding strength is not greater than 70 MPa, but is greater than 50 MPa but less than 70 MPa.

[0086] In mode 10, the bonding strength is 50 MPa or more and less than 70 MPa, which is sufficient strength. Fig.12 In the case of mode 10, Figure 1 This is a cross-sectional view of the SS after ultrasonic bonding, viewed in the direction of the arrow x.

[0087] It is considered that compared with other modes, if the depth t of the groove 1a formed before ultrasonic bonding is too large, the groove 1a will not be filled with the oxide 7 after ultrasonic bonding, forming a partial space, so the unbonded portion P with the base 2 increases, and therefore the bonding strength is not greater than 70 MPa, but becomes greater than 50 MPa and less than 70 MPa.

[0088] Next, use Fig.13 and Fig.14 Explain modes 11 to 15.

[0089] Fig.13 is from Figure 1 TT cross-sectional view after ultrasonic bonding as viewed in the z direction.

[0090] For modes 11 to 15, before ultrasonic bonding, w = 4.5 mm, wa / w = 2.2. It is assumed that ta / t is 21.3 in mode 11, 20.0 in mode 12, 12.5 in mode 13, 8.5 in mode 14, and 8.0 in mode 15.

[0091] The measurement results of the bonding strengths of Patterns 11 to 15 are described in sequence.

[0092] In modes 12 to 14, the excellent bonding strength was 70 MPa or more.

[0093] In mode 11, the bonding strength is 50 MPa or more and less than 70 MPa, which is sufficient. Fig.14 In the case of mode 11, Figure 1 This is a cross-sectional view of the SS after ultrasonic bonding, viewed in the direction of the arrow x.

[0094] It is considered that if the depth t of the groove 1a formed before ultrasonic bonding is too small compared to other modes, the oxide 7 fills the groove 1a and the oxide 7 beyond that remains on the bonding surface 5, so that the bonding strength becomes 50 MPa or more and less than 70 MPa.

[0095] It is 50 MPa or more and less than 70 MPa in Mode 15. It is considered that, compared with other modes, if the depth t of the groove portion 1a formed before ultrasonic bonding is too large, the groove portion 1a is not filled with the oxide 7 and a part of the space is formed. Therefore, the unbonded portion with the base 2 increases, and thus the bonding strength becomes 50 MPa or more and less than 70 MPa.

[0096] Next, use Fig.15 and Fig.16 to illustrate Modes 16 to 20.

[0097] Fig.15 is the T-T sectional view after ultrasonic bonding as viewed from the arrow direction of z of Figure 1 The S-S sectional view after ultrasonic bonding as viewed from the arrow direction of x of Fig.16 is from Figure 1 is the S-S sectional view after ultrasonic bonding as viewed from the arrow direction of x of

[0098] Regarding Modes 16 to 20, before ultrasonic bonding, let w = 5.0 mm and wa / w = 2.0. Let ta / t be 21.3 in Mode 16, 20.0 in Mode 17, 12.5 in Mode 18, 8.5 in Mode 19, and 8.0 in Mode 20.

[0099] The measurement results of the bonding strength of Modes 16 to 20 are described in sequence.

[0100] In all of Modes 16 to 20, it is 50 MPa or more and less than 70 MPa, which is sufficient strength. The reason is considered to be that, compared with other modes, if the number of groove portions 1a is smaller, the amount of oxide 7 filled into the groove portion 1a on the surface of the bonding surface 5 is more than the portion filled into the groove portion 1a. Therefore, the oxide 7 in the portion not filled into the groove portion 1a remains on the bonding surface 5.

[0101] The results obtained from the experiments of the above-mentioned Modes 1 to 20 are that, in order to make the bonding strength 50 MPa or more, it is preferable that the depth t of the groove portion 1a formed before ultrasonic bonding satisfies ta / 20 ≤ t < ta / 8, and the interval w between the formed multiple groove portions 1a satisfies wa / 5 ≤ w < wa / 2. In addition, after ultrasonic bonding, due to plastic flow, the t1 portion filled with the material of the metal component which is the material of the contact point 1 is 0.1×t ≤ t1 < 0.5×t.

[0102] After ultrasonic bonding, the t1 portion of the groove portion 1a on the surface side of the contact point 1 is filled with the material of the metal component contained in the material of the contact point 1 due to plastic flow, and the oxide film formed on the bonding surface 5 is included in the t2 portion of the groove portion 1a more internal than the surface side of the contact point 1 as the oxide 7, and is thus efficiently repelled.

[0103] Therefore, in the contact 6 of the present embodiment, no oxide film remains on the bonding surface 5 , and the bonding strength is improved.

[0104] Furthermore, when the contact 1 and the base 2 are joined, the time required for the bottom surface of the recessed portion of the contact to contact the base and abut against the ultrasonic horn 4 can be reduced, thereby enabling efficient manufacturing.

[0105] In the present embodiment, in the experiments with modes 1 to 20, the groove 1a formed in the joint 1 before ultrasonic bonding is set to a slit shape. The slit-shaped groove 1a is easy to manufacture on the joint 1, and since the slit shape is linear in the depth direction of the groove 1a before ultrasonic bonding, it is easy to take the oxide 7 into the groove 1a. Therefore, the groove 1a is preferably a slit shape, but it is not limited. The groove 1a can be formed along a predetermined pattern and can be changed arbitrarily. For example, Fig.17 and Fig.18 Another example of the shape of the groove portion 1 a after ultrasonic bonding is shown.

[0106] For example, Fig.17 is from Figure 1 SS cross-section after ultrasonic bonding viewed in the x direction. Fig.18 This is a cross-sectional view of the TT after ultrasonic bonding as viewed from the z direction. Fig.17 As shown in FIG. 1 , the groove portion 1a before ultrasonic bonding may not be linear but may be curved in the width direction of the groove portion 1a. Fig.18 As shown, the length in the z direction, which is the depth direction of the groove portion 1 a before ultrasonic bonding, may be formed to be smaller than the length of the joint 1 in the depth direction of the groove portion 1 a .

[0107] in addition, Fig.19 An example of a schematic diagram of a switch equipped with the contact 6 of this embodiment is shown. Fig.19 The interrupter shown in FIG. 1 is provided with a contact stage 8 that contacts the contact 1 in the closed state and a drive control device 9 that drives the base 2 that engages with the contact 1. In addition, the contact 1 may be engaged on the contact stage 8.

[0108] In addition, the range where the current flowing through the interrupter is concentrated varies depending on the parallelism and flatness of the contact stage 8 and the contact point 1. As a result, the amount of heat and impact applied to the contact point 1 varies depending on the range where the current is concentrated. Therefore, the depth t of the groove portion 1a before ultrasonic bonding can be arbitrarily changed depending on the contact surface of the contact stage 8 that contacts the contact point 1 when the interrupter is operating.

[0109] The interrupter using the contact 6 of this embodiment has oxide 7 introduced into the groove 1a formed on the surface of the contact 1 before ultrasonic bonding to increase the bonding strength between the contact 1 and the base 2, and thus becomes a more stable interrupter.

Claims

1. A method for manufacturing a contact, comprising: A step of forming a groove portion having a depth greater than a width from the surface of the contact on the surface of the contact; The step of placing the base on a mounting table of the ultrasonic bonder; a step of placing the contact point on the base on the mounting table in such a manner that the base contacts the surface on which the groove is formed; A step of bringing an ultrasonic horn of the ultrasonic bonder into contact with the contact point; and The step of applying ultrasonic energy from the ultrasonic horn to join the contact point and the base.

2. The method for manufacturing a contact according to claim 1, characterized in that: The width of the groove portion is 5 μm to 15 μm.

3. The method for manufacturing a contact according to claim 1, characterized in that: A plurality of the grooves are formed on the surface of the contact at intervals from each other in the width direction of the groove.

4. The method for manufacturing a contact according to claim 2, characterized in that: A plurality of the grooves are formed on the surface of the contact at intervals from each other in the width direction of the groove.

5. The method for manufacturing a contact according to claim 3, characterized in that: If the depth of the groove is t, and the length of the contact point in the depth direction of the groove is ta, then ta / 20≤t <ta / 8, If the length of the contact point in the width direction of the groove is wa, and the interval between the grooves is w, then wa / 5≤w <wa / 2。 6. The method for manufacturing a contact according to claim 4, characterized in that: If the depth of the groove is t, and the length of the contact point in the depth direction of the groove is ta, then ta / 20≤t <ta / 8, If the length of the contact point in the width direction of the groove is wa, and the interval between the grooves is w, then wa / 5≤w <wa / 2。 7. The method for manufacturing a contact according to any one of claims 1 to 6, characterized in that: The base is made of Cu as a main component and contains W and C.

8. The method for manufacturing a contact according to any one of claims 1 to 6, characterized in that: If the surface roughness of the surface of the contact point is defined as Ra, 5 μm ≤ Ra < 20 μm.

9. The method for manufacturing a contact according to any one of claims 1 to 6, characterized in that: The groove portion has a slit shape.

10. The method for manufacturing a contact according to any one of claims 1 to 6, characterized in that: The length in the depth direction of the groove portion, which is a direction perpendicular to the depth direction of the groove portion and the width direction of the groove portion, is equal to the length of the contact point in the depth direction of the groove portion.

11. The method for manufacturing a contact according to any one of claims 1 to 6, characterized in that: The length of the groove portion in the depth direction is smaller than the length of the contact point in the depth direction of the groove portion.

12. A contact comprising a base and a contact point ultrasonically bonded to the base, characterized in that: A groove is formed on the surface of the contact on the base side, and the groove includes a portion on the surface side filled with the material of the contact and a portion in which materials of the contact and the base and oxide are mixed compared to the surface side.

13. The contact according to claim 12, characterized in that: If the depth of the groove is t, and the portion of the groove filled with the material is t1, then 0.1×t≤t1<0.5×t.

14. An interrupter comprising: The contact member according to claim 12; a contact stage that contacts the contact point in a closed state; and The driving control device drives the base to open and close the contact piece.

Citation Information

Patent Citations

  • Binding contact material

    JP1991156815A

  • Ultrasonic welding / brazing a steel workpiece over aluminum alloys

    CN109807457A

  • Method and apparatus for ultrasonic-welding of metal

    JP2012223780A